A Comparative Study on the Relationship Between Learning Motivations and Outcomes of College Students in Taiwan and Shenzhen Region of Mainland China: Learning Modes as Mediators - Sophia Shi-Huei Ho; Yao-Ping Peng (National Taipei University of Education, 2016)
Previous studies in the relationship of learning motivation and outcome were mostly conducted on research samples in Asia from the perspective of oriental culture; however, under the same cultural background, different social systems might lead to different teaching and learning outcomes. Therefore, this study examines the learning motivation patterns of Taiwan and Mainland China college students from the perspectives on psychological motivation, and investigates the relationship between learning modes and learning outcomes. Adopting judgmental sampling, a total of 651 valid questionnaires were collected from cross-strait business college sophomore, junior, and senior students. The measurement scales were developed by Li et al. (2007), Nasir et al. (2009), Philip et al. (2008), Pike et al. (2011), White et al. (2008), and all measures were 5-point Likert-type scales. The path relationship of the two groups was examined through structural equation modeling (SEM) using AMOS. The results showed that exploitative learning was perceived as more effective by the college students in Taiwan as compared to those in Mainland China. In terms of academic identity, the contrary is the case. However, in path analysis, Taiwanese students were superior to Chinese students in regard to the positive influence of role identity on exploitative and explorative learning and the positive influence of exploitative learning on cognitive and non-cognitive gains.